SOCIAL ISSUES IN THE POETRY ANTHOLOGY SUARA DARI KELAS KECIL - Nurul Utami Khairunnisa; La Ode Syukur; Haerun Ana (Jurnal Casa Cendekia, 2026)
This study aims to describe the forms of social issues represented in the poetry anthology Suara dari Kelas Kecil. The research employs a qualitative descriptive method using a sociology of literature approach. The data consist of words, phrases, and poetic lines found in ten selected poems that reflect social realities and social criticism. Data were collected through library research and close reading techniques, then analyzed by classifying and interpreting the identified social issues based on their thematic relevance. The findings indicate that the poems in Suara dari Kelas Kecil portray various social issues that reflect contemporary societal conditions. These issues include poverty, crime, social conflict, violations of social norms, discrimination, and corruption. Poverty is depicted through the portrayal of marginalized groups struggling to meet basic needs, while crime and corruption are presented as structural problems resulting from weak moral values and ineffective governance. Social conflict and norm violations emerge from injustice and power imbalance, whereas discrimination reflects unequal treatment toward certain social groups. This study concludes that the poems in Suara dari Kelas Kecil function not only as aesthetic literary expressions but also as a medium of social criticism that voices the concerns of marginalized communities. Through a sociology of literature perspective, the anthology demonstrates that poetry plays a significant role in reflecting social realities and fostering critical awareness among readers regarding ongoing social problems.